THE ROLE OF PERSONALITY IN THE ADAPTATION TO RETIREMENT - Henning, G. (Innov Aging, 2017)
While personality has been believed to moderate individual adjustment to retirement, no prospective study has yet investigated this assumption. We used data from two waves of the HEARTS (Health, Aging, and Retirement Transitions in Sweden) study (N=5.913, Age 60–66). We applied latent profile analysis to find personality profiles based on the Big 5 personality traits with data from the first wave. The analysis supports a four class solution. In preliminary analyses, we find personality profile to predict depressive symptoms both cross-sectionally and prospectively. Furthermore, we find that involuntary retirement between waves is associated with an increase in depressive symptoms. Persons with a specific personality profile (so called “undercontrollers”), experience stronger effects of involuntary retirement. Further effects and possible pathways will be investigated next and presented at the conference.